2019
DOI: 10.3390/diagnostics9010013
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Efficient and Easy to Perform PCR-Based Assay to Identify Met Exon 14 Skipping in Formalin-Fixed Paraffin-Embedded (FFPE) Non-Small Cell Lung Cancer (NSCLC) Samples

Abstract: MET is a receptor tyrosine kinase (RTK) that plays important roles in carcinogenesis. Despite being frequently overexpressed in cancer, clinical responses to targeting this receptor have been limited. Recently novel splicing mutations involving the loss of exon 14 (called METex14 skipping) have emerged as potential biomarkers to predict for responsiveness to targeted therapies with Met inhibitors in non-small cell lung cancer (NSCLC). Currently, the diverse genomic alterations responsible for METex14 skipping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…All patients provided written informed consent. MET Δex14 status and MET GCN were assessed from formalin‐fixed, paraffin‐embedded human tissue at a central laboratory at enrollment by quantitative real‐time RT‐PCR and fluorescence in situ hybridization, respectively 41 . All patients were administered capmatinib 400 mg tablets twice daily in fasting conditions in 21‐day cycles, except in cohorts 6 and 7 where capmatinib was administered regardless of fasting status.…”
Section: Methodsmentioning
confidence: 99%
“…All patients provided written informed consent. MET Δex14 status and MET GCN were assessed from formalin‐fixed, paraffin‐embedded human tissue at a central laboratory at enrollment by quantitative real‐time RT‐PCR and fluorescence in situ hybridization, respectively 41 . All patients were administered capmatinib 400 mg tablets twice daily in fasting conditions in 21‐day cycles, except in cohorts 6 and 7 where capmatinib was administered regardless of fasting status.…”
Section: Methodsmentioning
confidence: 99%
“…Until recently, screening for MET exon 14 skipping was technically challenging. Despite being appropriate for analyzing MET overexpression [84], immunohistochemistry has proved unsuitable for detecting MET exon 14 skipping, as, so far, anti-MET antibodies are not able to distinguish the exon 14-skipped splice variant from wild-type MET [85]. DNA-or RNA-based approaches are more appropriate.…”
Section: Challenges Ahead For Trials Of Met Inhibitors In Patients With Met Exon 14 Skipping Tumorsmentioning
confidence: 99%
“…RNA-based approaches need only to detect the fusion of exons 13 and 15 in the transcribed product [86]. As such, RNA in situ hybridization is possible [85], although RT-PCR-based sequencing approaches are also commonly used [86,87]. However, high-quality RNA is harder to obtain than DNA, as RNA is more susceptible to degradation [86,88].…”
Section: Challenges Ahead For Trials Of Met Inhibitors In Patients With Met Exon 14 Skipping Tumorsmentioning
confidence: 99%
“…IHC is only able to detect MET overexpression, which may occur due to not only METex14 alterations but also increased gene copy number and gene amplification. 24 Several studies have shown MET IHC overexpression poorly predicts for the presence of METex14 alterations. [25][26][27] Furthermore, there may be a high degree of inter-observer variability in the interpretation of IHC.…”
Section: Molecular Diagnostic Approaches For Metex14 Skipping Alteratmentioning
confidence: 99%
“…RNA-based methods of detecting METex14 skipping mutations such as quantitative PCR assays 24 , 37 are based on the detection of a fusion transcript, which in this case, is between MET exon 13 and 15. As such, the interpretation of this assay is more straightforward than that of DNA-based assays for screening purposes.…”
Section: Molecular Diagnostic Approaches For Metex14 Skipping Alteratmentioning
confidence: 99%